Atomic-resolution evaluation of microsegregation and degree of atomic order at antiphase boundaries in Ni50Mn20In30 Heusler alloy. (1st January 2017) - Niitsu, K.; Minakuchi, K.; Xu, X.; Nagasako, M.; Ohnuma, I.; Tanigaki, T.; Murakami, Y.; Shindo, D.; Kainuma, R.
Abstract: The atomic arrangement and microsegregation in the vicinity of thermally induced antiphase boundaries in a Ni50 Mn20 In30 Heusler alloy are investigated through multislice simulations, high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), X-ray diffraction pattern Rietveld analysis, energy-dispersive X-ray spectroscopy, and modified Bragg–Williams–Gorsky calculations. Intensity analysis of atomic-resolution HAADF-STEM images revealed that a 180° geometrical phase shift occurred across the antiphase boundaries, accompanied by a decay in the degree of atomic order and an enrichment of In. Energy-dispersive (X-ray) spectroscopy analysis revealed an In enrichment as high as 2.7 at.% at the center of the antiphase boundaries, comparable to that (1.0–1.8 at.%) suggested by the parallel tangent law for the Gibbs energy curves of the L 21 and B 2 phases using the modified Bragg–Williams–Gorsky calculation. This suggests that microsegregation occurs at the antiphase boundaries and can be understood basically within the framework of the local thermodynamic equilibrium. Graphical abstract: Image 1